Synthesis and Characterization of Thioamide Bands in Cr(III) and V(V) Complexes with O- and N-Donor Ligands - Pathak, Vishal; Yadav, D.C.; Gupta, M.P.; Srivastava, B.K. (Asian Journal of Chemistry, 2010)
Complexes of chromiurn(III) and vanadiurn(V) with thiourea have been synthesised in acidic, neutral and alkaline media and charactrised by elemental analysis, magnetic measurement, electronic, IR, 1H NMR, UV-visible studies. The v(NH) band and thioarnide bands I, II, III and IV of the free ligand and their complexes have been analysed and the nature of metal-ligand bondings has been determined in the present paper.